A Beauvoirian Feminist Analysis of Women’s Representation in William Faulkner’s “A Rose for Emily” - Nafdi Irawan; Afriana Afriana (eScience Humanity Journal, 2025)
This study analyzes the representation of women in William Faulkner’s A Rose for Emily through Simone de Beauvoir’s feminist theoretical framework. Employing Beauvoir’s concepts of the Other, myths of woman, and women’s categorization as prostitute, the research examines women's representation reflected in the narrative that frames the story of Faulkner's A Rose for Emily, and unveils the perspective of Faulkner as the male author on women as implied in the story. The data are collected through the primary source involved close reading of Faulkner's "A Rose for Emily". The analysis reveals that the protagonist (Emily) is positioned as the Other within a patriarchal social structure that deprives women's autonomy, confined within cultural myth of women reproduced to maintain male domination and reinforce women subordinate positions. Faulkner, as the male author, reflects his perspectives in between of perpetuation and resistance to the social construction of women. The analysis also uncovers Faulkner’s ambivalent perspective as the male author. In certain narrative elements, he seems to perpetuate patriarchal constructions, while in other aspects, he implicitly challenges these norms through the protagonist's (Emily) acts of resistance against social constraints. Overall, the result demonstrates that Faulkner’s narrative both reflects and critiques the power of gender and its relations within a socio-historical context.